Recruitment Sources and Teachers’ Performance in Dawakin Kudu Local Government Education Authority, Kano State, Nigeria - Umar Umar Abdulkadir (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
The effectiveness of educational systems largely depends on the quality and performance of teachers, which are influenced by the methods used to recruit them. However, finding a qualified candidate who eventually performs better is complex. The primary objective of this study was to evaluate the various sources that influence candidate selection and directly impact teachers' performance. The study employed a cross-sectional survey Design. Stratified sampling was used in selecting the sample of respondents. The table by Gill et al. was used to determine the sample size. The study employed a questionnaire to collect data. Inferential statistics were employed in the data analysis, utilising simple linear regression in SPSS version 25. The study found a significant effect of the source of candidate selection on teachers' performance in the Dawakinkudu Local Government Education Authority of Kano, Nigeria. The study also recommends that candidate selection should be strictly and consistently based on merit rather than favouritism or who you know.